In vitro modeling of hepatocellular carcinoma niche on decellularized tomato thorny leaves: a novel natural three-dimensional (3D) scaffold for liver cancer therapeutics - Ahmadian, Mariye; Hosseini, Saadi; Alipour, Atefeh; Jahanfar, Mehdi; Farrokhi, Naser; Homaeigohar, Shahin; Shahsavarani, Hosein (Frontiers in Bioengineering and Biotechnology, 2023)
Liver cancer is now one of the main causes leading to death worldwide. To achieve reliable therapeutic effects, it is crucial to develop efficient approaches to test novel anticancer drugs. Considering the significant contribution of tumor microenvironment to cell's response to medications, in vitro 3D bioinspiration of cancer cell niches can be regarded as an advanced strategy to improve the accuracy and reliability of the drug-based treatment. In this regard, decellularized plant tissues can perform as suitable 3D scaffolds for mammalian cell culture to create a near-to-real condition to test drug efficacy. Here, we developed a novel 3D natural scaffold made from decellularized tomato hairy leaves (hereafter called as DTL) to mimic the microenvironment of human hepatocellular carcinoma (HCC) for pharmaceutical purposes. The surface hydrophilicity, mechanical properties, and topography measurement and molecular analyses revealed that the 3D DTL scaffold is an ideal candidate for liver cancer modeling. The cells exhibited a higher growth and proliferation rate within the DTL scaffold, as verified by quantifying the expression of related genes, DAPI staining, and SEM imaging of the cells. Moreover, prilocaine, an anticancer drug, showed a higher effectiveness against the cancer cells cultured on the 3D DTL scaffold, compared to a 2D platform. Taken together, this new cellulosic 3D scaffold can be confidently proposed for chemotherapeutic testing of drugs on hepatocellular carcinoma.